Ōoku : the Inner Chambers. Vol. 1 - Yoshinaga, Fumi, 1971- (Viz Media, 2009)
"In Edo period Japan, a strange new disease called the Red Pox has begun to prey on the country's men. Within eighty years of the first outbreak, the male population has fallen by seventy-five percent. Women have taken on all the roles traditionally granted to men, even that of the Shogun. The men, precious providers of life, are carefully protected. And the most beautiful of the men are sent to serve in the Shogun's Inner Chamber"--Cover.